An Analysis of Sentence Types Production and Speech Disorders Characteristics in Wernicke’s Aphasia Sufferer - Anwar, Salma Ramadanti; Widianingsih, Ayang Winda Sri; Nurfithri, Nurfithri (Ma'soem University, 2024)
Wernicke's aphasia is a speech disorder with speech that is quite fluent but has a meaning that does not make sense. Many utterances are just the contents of the sufferer's thoughts. This analysis focuses on the characteristics of sentence production and speech disorders in individuals with Wernicke's aphasia. Individuals with Wernicke's aphasia suffer from a language disorder that affects their ability to communicate effectively. Their speech is typically fluent but nonsensical, and they may struggle to find the right words or understand what is being said to them. They may also make errors in their speech and be unaware of these mistakes, which can make communication even more challenging. Additionally, their sentence structure, grammar, and syntax can be compromised, leading to structurally deficient sentences. Limited use of functional words, the presence of neologisms, and perseveration contribute to the incoherence of their speech. Understanding these characteristics is crucial for developing targeted interventions to enhance communication for individuals with Wernicke's aphasia. The results of this research found that there are 7 types of sentence patterns, 5 types of sentences based on their function and structure, and 4 characteristics of speech disorders that appear in the utterances expressed by Byron.